Penyitaan Aset Hasil Tindak Pidana Korupsi oleh Komisi Pemberantasan Korupsi terhadap Aparatur Sipil Negara sebagai Upaya Pemberantasan Korupsi di Indonesia - Tubagus Ahmad Suhendar (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
ABSTRACT This study aims to analyze the confiscation of assets derived from corruption by the Corruption Eradication Commission (KPK) against Civil Servants (ASN) as an effort to combat corruption in Indonesia. Corruption is categorized as an extraordinary crime that not only causes financial losses to the state but also hinders national development and reduces public trust in government institutions. Therefore, a comprehensive approach is required to eradicate corruption, one of which is through asset recovery mechanisms. This research employs a normative juridical method using statutory and conceptual approaches. The data used are secondary data obtained through library research, including primary, secondary, and tertiary legal materials. The data are analyzed qualitatively using a descriptive-analytical method to provide a comprehensive understanding of asset confiscation in corruption cases. The results indicate that asset confiscation plays a crucial role in recovering state losses caused by corruption. However, in practice, asset confiscation faces various challenges, including difficulties in evidence collection, regulatory limitations, and weak coordination among law enforcement agencies. Furthermore, the Indonesian legal system, which still relies on an in personam approach, requires a final court decision before asset confiscation can be executed. As an alternative, the concepts of Non-Conviction Based Asset Forfeiture (NCB) and the follow the money approach are considered more effective in supporting asset recovery. Therefore, comprehensive legal reform, strengthening of regulations, and enhancement of law enforcement capacity are necessary. In conclusion, asset confiscation can serve as an effective instrument in combating corruption and promoting a fair and integrity-based legal system in Indonesia.